2012
DOI: 10.1038/onc.2012.284
|View full text |Cite
|
Sign up to set email alerts
|

Arg/Abl2 promotes invasion and attenuates proliferation of breast cancer in vivo

Abstract: Tumor progression is a complex, multistep process involving accumulation of genetic aberrations and alterations in gene-expression patterns leading to uncontrolled cell division, invasion into surrounding tissue and finally dissemination and metastasis. We have previously shown that the Arg/Abl2 non-receptor tyrosine kinase acts downstream of the EGF receptor and Src tyrosine kinases to promote invadopodium function in breast cancer cells, thereby promoting their invasiveness. However, whether and how Arg cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 35 publications
7
124
2
Order By: Relevance
“…Here we show, possibly for the first time, that ABL kinases are required for cancer cell extravasation. This finding is in contrast with a report showing that loss of ABL2 does not affect extravasation of breast cancer cells (43). We previously reported that ABL kinases are required for metastatic colonization of breast cancer cells in bone (44).…”
Section: Discussioncontrasting
confidence: 99%
“…Here we show, possibly for the first time, that ABL kinases are required for cancer cell extravasation. This finding is in contrast with a report showing that loss of ABL2 does not affect extravasation of breast cancer cells (43). We previously reported that ABL kinases are required for metastatic colonization of breast cancer cells in bone (44).…”
Section: Discussioncontrasting
confidence: 99%
“…18 The disease phenotype and progression of MuLV are reminiscent, but not identical, of the disease phenotype in chronic myeloid leukemia (CML) and Ph+ acute lymphoblastic leukemia (ALL), which is mediated by an independent N-terminal fusion of Bcr to Abl. 19 In contrast to CML and Ph+ ALL where Abl is a driver mutation, in solid cancers such as melanoma, 20,21 nonsmall cell lung cancer, 22 colorectal cancer, 23 and breast cancer, [24][25][26] Abl is activated downstream of activated growth factor receptors, as outlined by Plattner in this monograph. The mechanisms by which growth factor receptors activate Abl are multifactorial.…”
Section: Monographsmentioning
confidence: 99%
“…Abl kinases also regulate motility, invasion and metastasis of solid tumors; knockdown of ABL2 alone decreases cancer cell invasion and intravasation following implantation of MDA-MB-231 breast cancer cells in the mammary fat pad (Gil-Henn et al, 2013). Moreover, Abl kinases have been shown to promote invasion and metastasis of melanoma cells (Fiore et al, 2014).…”
Section: Role For Abl Kinases In Solid Tumorsmentioning
confidence: 99%